2012
DOI: 10.1124/jpet.112.198341
|View full text |Cite
|
Sign up to set email alerts
|

Na+,K+-ATPase Functionally Interacts with the Plasma Membrane Na+,Ca2+ Exchanger to Prevent Ca2+ Overload and Neuronal Apoptosis in Excitotoxic Stress

Abstract: Using a fluorescent viability assay, immunocytochemistry, patch-clamp recordings, and Ca 2ϩ imaging analysis, we report that ouabain, a specific ligand of the Na ϩ ,K ϩ -ATPase cardiac glycoside binding site, can prevent glutamate receptor agonistinduced apoptosis in cultured rat cortical neurons. In our model of excitotoxicity, a 240-min exposure to 30 M N-methyl-Daspartate (NMDA) or kainate caused apoptosis in ϳ50% of neurons. These effects were accompanied by a significant decrease in the number of neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 53 publications
(103 reference statements)
6
69
0
1
Order By: Relevance
“…Given the preferential contribution of GluN2A-containing NMDARs to the HCY effects, this amino acid is expected to be much less efficient neurotoxicant, than NMDA. In consistence to achieve the similar levels of apoptosis in primary culture of rat cortical neurons a 24-h exposure to HCY was required (Abushik et al, 2014), instead of a 4-h exposure to NMDA (Sibarov et al, 2012). Unlike NMDA-induced excitotoxicity is sensitive to NMDAR inhibitors (Church et al, 1988; Mironova et al, 2007), apoptosis caused by HCY is highly sensitive to the mGluR5 antagonist MTEP (Abushik et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given the preferential contribution of GluN2A-containing NMDARs to the HCY effects, this amino acid is expected to be much less efficient neurotoxicant, than NMDA. In consistence to achieve the similar levels of apoptosis in primary culture of rat cortical neurons a 24-h exposure to HCY was required (Abushik et al, 2014), instead of a 4-h exposure to NMDA (Sibarov et al, 2012). Unlike NMDA-induced excitotoxicity is sensitive to NMDAR inhibitors (Church et al, 1988; Mironova et al, 2007), apoptosis caused by HCY is highly sensitive to the mGluR5 antagonist MTEP (Abushik et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, its IC 50 for fish NCXs is 1.9 and 3 mM for the reverse and forward modes of action, respectively (Abramochkin et al, 2013). In cultured cortical neurons, 10 mM KBR caused an immediate rise of intracellular Ca 21 , suggesting inhibition of NCX forward mode of transport (Sibarov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Then changes in NCXs described above are only a part of the mechanisms implicated in the process by which MSG-treated rats are more susceptible to seizures induced by 4-AP [44]. Furthermore, because neural depolarization may induce inversion of NCXs and the inversion may increase firing probability [75, 76], changes induced by MSG treatment as increased average frequency of basal EEG activity in both studied cerebral regions (reported here for first time; Table 1), suggest that the probability of NCXs inversion could be potentiated after the treatment; however this suggestion should be proved.…”
Section: Discussionmentioning
confidence: 99%
“…On the other wise, in vitro approaches have demonstrated that low concentrations (<1 μM) of KB-R7943 predominantly block the reverse mode of NCX3 [81], avoiding the rise in [Ca 2+ ] i and reducing the frequency of excitatory postsynaptic currents, but high concentrations (≥10 μM) can block both the reverse and forward modes of the NCXs and promote increases in both [Ca 2+ ] i and the frequency of excitatory postsynaptic currents [76]. Because very few studies have applied KB-R7943 intracerebrally, we are not able to specifically propose how KB-R7943 is exerting its effects on the seizures.…”
Section: Discussionmentioning
confidence: 99%